Kondisi Filariasis Pasca Pengobatan Massal di Kelurahan Pabean Kecamatan Pekalongan Utara Kota Pekalongan - Bondan Fajar Wahyudi; Nova Pramestuti (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2016)
Pekalongan city is endemic for filariasis. Filariasis Mass Drug Administration (MDA) implemented to decrease filariasis endemicity in Pekalongan. It was started in 2011, but in the Pabean Village has started implementing in 2009. The study aimed to determine filariasis condition after MDA. A descriptive study with cross sectional design was conducted in Pabean village, North Pekalongan Sub-district, Pekalongan city. Finger Blood Filariasis slide and medication status of those who had filariasis MDA in 2011-2013 were examined. Finger Blood Filariasis slide of 519 respondents examined found 7 (Mf rate 1.35 %) microfilariae positive and spread almost evenly throughout the village. Microfilariae density accounted for 229.02 per ml of blood and only one species of filarial worms found as Wuchereriabancrofti. Respondents who received the drug in 2011, 2012, and 2013 increased (80.02 %, 90.75 %, 92.68 % respectively), but respondents who were taking medication decreased (63.01 %, 60.89 %, and 55. 88 % respectively). Pabelan village still endemic filariasis (Mf rate > 1%) although MDA filariasis was done for 5 years.